The Effect Of The Project Based Learning Model Assisted By Crossword Puzzle Media On The Learning Outcomes Of Grade V Students - Sari Wahyuni; Aprima Tirsa (Universitas Islam Ahmad dahlan, 2026)
This study is to find out whether there is an influence of the Project Based Learning model assisted by crossword puzzle media on the learning outcomes of Class V students of SDN 2 Nanga Man. The research method uses a quantitative approach with a One Group pretest and posttest experimental design. The sample consisted of 17 students. “The research instrument was in the form of multiple-choice questions (pretest and posttest), validated through Cronbach Alpha constructs and reliability. Data analysis was carried out with the help of SPSS 25 through the Normality Test (Shapiro-Wilk), and the Non-Parametric Test (Wilcoxon Signed-Rank). The results showed that the shapiro-wilk test for pretest data was 0.031, meaning that the pretest data was not normally distributed. Meanwhile, the posttest data has a significance value of 0.738, meaning that the posttest data is normally distributed. The results of the” Wilcoxon Signed Rank Test were obtained at -3,630 with a significance value of Asymp. Sig. (2-tailed) is 0.000. So it can be concluded that there is a significant difference between student learning outcomes before and after the implementation of the Project Based Learning model assisted by Crossword Puzzle media.